Expression of Neuropeptide Y of GIFT Tilapia (Oreochromis sp.) in Yeast Pichia Pastoris and Its Stimulatory Effects on Food Intake and Growth - Wang, Guangzhong; Sun, Caiyun; Lin, Haoran; Li, Wensheng (IntechOpen, 2011)
None